GATA Binding Protein 3 Is a Direct Target of Kruppel-Like Transcription Factor 7 and Inhibits Chicken Adipogenesis - Sun, Yingning; Jin, Zhao; Zhang, Xinyang; Cui, Tingting; Zhang, Wenjian; Shao, Shuli; Li, Hui; Wang, Ning (Frontiers in Physiology, 2020)
Kruppel-like transcription factor 7 (KLF7) is a negative regulator of adipogenesis, however, its precise mechanism is poorly understood. Our previous KLF7 ChIP-seq analysis showed that one of the KLF7 binding peaks was present upstream of GATA binding protein 3 (GATA3) in chicken preadipocytes. In the present study, we identified GATA3 as a target of KLF7. Overexpression analysis showed KLF7 markedly enhanced the endogenous expression of GATA3 in the immortalized chicken preadipcyte cell line (ICP2), and the luciferase reporter assay showed that KLF7 overexpression increased the reporter gene activity of the cloned upstream region (-5285/-4336 relative to the translation initiation codon ATG) of GATA3 in ICP2 and DF1 cells, and mutation of the putative KLF7 binding site abolished the promotive effect of KLF7 overexpression on the reporter gene activity of the cloned GATA3 upstream region. ChIP-qPCR further demonstrated that KLF7 directly bound to the GATA3 upstream region. Gene expression analysis showed that GATA3 mRNA expression in abdominal adipose tissue was significantly higher in lean chicken line than in the fat line at 2, 3 and 6 weeks of age. In addition, GATA3 mRNA expression markedly decreased during the preadipocyte differentiation. Furthermore, a functional study showed that GATA3 overexpression inhibited the differentiation of the ICP2 cells. Taken together, our results demonstrated that KLF7 inhibits chicken adipogenesis, at least in part through direct upregulation of GATA3.